From Tyrian Purple to Kinase Modulators: Naturally Halogenated Indirubins and Synthetic Analogues - Vougogiannopoulou, Konstantina; Skaltsounis, Alexios-Leandros (Planta Medica, 2012)
Indirubins represent a small category of compounds with significant pharmacological activity focusing on the inhibition of protein kinases. A series of derivatives has been developed during the last 15 years aiming the investigation and amelioration of the indirubin scaffold in terms of activity, selectivity, and drug-likeness. The current article focuses on the naturally brominated indirubins present in the famous historic dye of Tyrian purple, attempting to gather all available literature regarding biosynthesis, isolation, and synthesis of related analogues. Halogenated indirubins are by far one of the most important subcategories of indirubins, with its main representatives 6-bromoindirubin (6BI) and 6-bromoindirubin-3′-oxime (6BIO) possessing an increased selectivity against GSK-3. This review attempts to summarize concisely structure/activity relationships among closely related halogenated analogues in terms of protein kinase inhibition and selectivity, while it also focuses on the various biological applications arising from the interactions of halogenated indirubins with molecular targets. Those include effects of halogenated indirubins on stem cells, cardiac, renal, and pancreatic cells, on leukemia and solid tumors, and on neurodegeneration.
Keywords: Indirubin; indigo; Tyrian purple; Hexaplex trunculus; Bolinus brandaris; Muricidae; protein kinases; CDKs; GSK-3β; stem cells